Dental markers of biocultural sex differences in an early modern population from Gothenburg, Sweden: caries and other oral pathologies - Carolina Bertilsson; Lisa Nylund; Maria Vretemark; Peter Lingström (BMC, 2021)
Abstract Background With the aim to study dental pathological lesions in an early Swedish modern population, with special reference to sex variances of dental caries, the prevalence and distribution of dental caries and tooth wear were determined in complete and partial human dentitions from an early modern-time city graveyard (1500-1620) excavated in Gamlestaden, Gothenburg, Sweden. Methods Partial and complete dentitions were examined through visual inspection and using a dental probe. Pathologies were studied, evaluated and presented by teeth and alveoli. Results The study population consisted of 308 individuals. A total of 4,951 teeth in adults and 1,660 teeth in children were examined. Caries prevalence in the studied population was 55% and the highest prevalence of caries was found among the adults, where 68% of the individuals had at least one carious lesion. Caries experience (DMT > 0) in the entire population was 60%, and among adults caries experience was 76%. Women had significantly higher caries experience than men (p < 0.05). Caries was most prevalent in the molar teeth and least prevalent in the incisors and canines. Significant age-related increases in tooth wear were found, and a positive correlation between wear in molars and incisors (p < 0.001). Other clinical findings were signs of apical lesions, crowding of teeth, aplasia, non-erupted canines and calculus. Conclusions Findings show that dental pathological lesions affected a majority of the studied population, and indicate that women were more predisposed to dental disease than their male counterparts. Results are discussed from a multi-factorial explanation model including dietary, physiological and cultural etiological factors.